Measuring roof-bolt response to axial and shear stresses: Laboratory and first in-situ analyses - Jessu, Kashi Vishwanath; Kostecki, T.; Spearing, Sam (Canadian Institute of Mining, Metallurgy and Petroleum, 2016)
Roof bolts are subjected to axial stresses, shear stresses, or both. Axial and shear stresses were compared between roof bolts machined with two and three slots. Shear stresses perpendicular to and at an angle to the shear planes were evaluated by analyzing a three-slot instrumented roof bolt, performing laboratory tests on two- and three-slot roof bolts, and conducting in-situ test analyses. Three-slot bolts appear to provide a complete bending strain profile, requiring no prior knowledge of the estimated shear-plane orientation. Minimum displacements occur in roof bolts installed perpendicular to rather than at an angle to the shear planes.